2007
DOI: 10.3402/ijch.v66i1.18228
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient intakes are associated with adherence to a traditional diet among Yup`ik Eskimos living in remote Alaska Native communities: the CANHR Study

Abstract: Objectives. To determine whether dietary westernization is associated with intake of select nutrients among Alaska Natives living in remote communities. To investigate participant characteristics associated with adherence to the traditional Alaska Native diet. Study Design. Cross-sectional survey. Methods. A 24-hour recall was collected from 241 men and 307 women aged 14-94 years living in seven remote communities of Western Alaska. Bivariate analyses and ANOVA were used to examine the relationship between ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
119
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 104 publications
(132 citation statements)
references
References 12 publications
13
119
0
Order By: Relevance
“…How?Food security measured? How?Food security pillarQuantitative traditional food intake articlesBallew et al [3]The Alaska Traditional Diet Survey13 Remote villages statewideAlaska Native women (n=401) and men (n=253) aged 13–88 yearsYes – interviewer administered FFQ with portion sizes over the past 12 monthsNoFood access and food utilisationBartell et al [22]What People Eat: atka, Alaska, 1998–19991 Remote community in the Aleutians34 of the 80 residents in Atka of unknown agesYes – FFQ and a 24-h recallNoFood utilisationBersamin et al [23]The Center for Alaska Native Health Research Pilot Study3 Remote communities in SW AlaskaAlaska Native women (n=44) and men (n=48), aged 14–81 yearsYes – single 24-h recallNoFood utilisationBersamin et al [4]The Center for Alaska Native Health Research Study7 Remote communities in SW AlaskaAlaska Native women (n=307) and men (n=241), aged 14–94 yearsYes – single 24-h recallNoFood utilisationBersamin et al [43]The Center for Alaska Native Health Research Study7 Remote communities in SW AlaskaAlaska Native women (n=301) and men (n=230), aged 14–94 yearsYes – 24-h recall and a 3-day food from 54% of the participantsNoFood utilisationEliat-Adar et al [44]Genetics of Coronary Artery Disease in Alaska Natives (GOCADAN) Stud7 Remote villages in the Norton Sound regionAlaska Native women (n=677) and men (n=537), aged 18 years and olderYes – FFQ from previous year; 97 food items classified into 28 food groupsNoFood utilisationHeller and Scott [20]The Alaska Dietary Survey: 1956–196111 Rural villages in AlaskaAlaska Native women and men, children and adultsYes – diet records of 3–7 day duration; collected on a seasonal basisNoFood utilisationJohnson et al […”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…How?Food security measured? How?Food security pillarQuantitative traditional food intake articlesBallew et al [3]The Alaska Traditional Diet Survey13 Remote villages statewideAlaska Native women (n=401) and men (n=253) aged 13–88 yearsYes – interviewer administered FFQ with portion sizes over the past 12 monthsNoFood access and food utilisationBartell et al [22]What People Eat: atka, Alaska, 1998–19991 Remote community in the Aleutians34 of the 80 residents in Atka of unknown agesYes – FFQ and a 24-h recallNoFood utilisationBersamin et al [23]The Center for Alaska Native Health Research Pilot Study3 Remote communities in SW AlaskaAlaska Native women (n=44) and men (n=48), aged 14–81 yearsYes – single 24-h recallNoFood utilisationBersamin et al [4]The Center for Alaska Native Health Research Study7 Remote communities in SW AlaskaAlaska Native women (n=307) and men (n=241), aged 14–94 yearsYes – single 24-h recallNoFood utilisationBersamin et al [43]The Center for Alaska Native Health Research Study7 Remote communities in SW AlaskaAlaska Native women (n=301) and men (n=230), aged 14–94 yearsYes – 24-h recall and a 3-day food from 54% of the participantsNoFood utilisationEliat-Adar et al [44]Genetics of Coronary Artery Disease in Alaska Natives (GOCADAN) Stud7 Remote villages in the Norton Sound regionAlaska Native women (n=677) and men (n=537), aged 18 years and olderYes – FFQ from previous year; 97 food items classified into 28 food groupsNoFood utilisationHeller and Scott [20]The Alaska Dietary Survey: 1956–196111 Rural villages in AlaskaAlaska Native women and men, children and adultsYes – diet records of 3–7 day duration; collected on a seasonal basisNoFood utilisationJohnson et al […”
Section: Resultsmentioning
confidence: 99%
“…A majority (n=13) of the research that estimated traditional food intake found that people who consumed traditional foods had higher intakes of several important nutrients, including protein, omega-3 fatty acids and iron [3,4,20,21]. Other articles compared the dietary intake of people who consumed traditional foods against a national sample or national recommendations [20,22–25] and in many situations concluded that traditional foods help to meet these recommendations, especially for energy, protein and fat intake (n=9) [21,2527].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations